Association between radiographic joint space narrowing, function, pain and muscle power in severe osteoarthritis of the knee. - Barker, K; Lamb, S; Toye, F; Jackson, S; Barrington, S (2004)
OBJECTIVE: To examine the association between radiographic classification of severe knee osteoarthritis and measurements of function, pain and power. DESIGN: Cross-sectional study. SETTING: Specialist orthopaedic hospital. SUBJECTS: One hundred and twenty-three patients on the waiting list for elective knee arthroplasty. OUTCOME MEASURES: Weight-bearing antero-posterior radiographs scored for severity of osteoarthritis using the Kellgren and Lawrence scale. Function measured using the function subscale of the WOMAC (Western Ontario and McMaster Universities) index, timed tests of walking speed and sit-to-stand. Pain measured using the pain subscale of the WOMAC index and a visual analogue scale. Extensor strength of the lower limb measured with the leg extensor power rig. RESULTS: Within any radiographic grade there was considerable variation in function: WOMAC function for patients with grade 2 mean 64 (47-86), grade 3 mean 47 (12-89) grade 4 mean 45 (2-92). There was poor correlation between radiographic score function, pain or muscle power, with no statistically significant associations. A wide range of scores was also seen within patients with the same radiographic grade. CONCLUSIONS: Radiographic score was not found to be closely associated with function. Amongst patients with the same radiographic score there was considerable variation in function, pain and power.